2019
DOI: 10.1152/ajpendo.00227.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac overexpression of perilipin 2 induces atrial steatosis, connexin 43 remodeling, and atrial fibrillation in aged mice

Abstract: Atrial fibrillation (AF) is prevalent in patients with obesity and diabetes, and such patients often exhibit cardiac steatosis. Since the role of cardiac steatosis per se in the induction of AF has not been elucidated, the present study was designed to explore the relation between cardiac steatosis and AF. Transgenic (Tg) mice with cardiac-specific overexpression of perilipin 2 (PLIN2) were housed in the laboratory for more than 12 mo before the study. Electron microscopy of the atria of PLIN2-Tg mice showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Calcium channel protein levels and related miRNAs were regulated in older patients, suggesting their function with aging in AF occurrence 102 . Perilipin 2, a lipid droplet protein, was recently demonstrated to contribute to the lateralization of connexin 43 (Cx43), evoking conduction slowing, which could explain the AF vulnerability of aged perilipin 2‐transgenic mice 103 . Because perilipin is one of the main proteins involved in lipid accumulation in adipocytes, these results suggest the role of local fat in Cx43 lateralization in AF cardiomyocytes.…”
Section: Pathophysiological Mechanisms Of Af Related To Eatmentioning
confidence: 99%
“…Calcium channel protein levels and related miRNAs were regulated in older patients, suggesting their function with aging in AF occurrence 102 . Perilipin 2, a lipid droplet protein, was recently demonstrated to contribute to the lateralization of connexin 43 (Cx43), evoking conduction slowing, which could explain the AF vulnerability of aged perilipin 2‐transgenic mice 103 . Because perilipin is one of the main proteins involved in lipid accumulation in adipocytes, these results suggest the role of local fat in Cx43 lateralization in AF cardiomyocytes.…”
Section: Pathophysiological Mechanisms Of Af Related To Eatmentioning
confidence: 99%
“…Based on the relationship between adipose tissue components and the presence of AF, various groups have investigated specific factors that regulate atrial electrical remodeling, and the associations between adipose tissue and regulation of Cx43 expression and/or activity during AF [119,120].…”
Section: Obesity Atrial Fibrillation and CXmentioning
confidence: 99%
“…More recently, Sato et al [120] studied the relationship between cardiac steatosis and AF in mice overexpressing Perilipin 2 (PLIN2). In their study, transgenic mice showed increased atrial fat accumulation and electrocardiographic abnormalities, with a higher prevalence of persistent AF.…”
Section: Obesity Atrial Fibrillation and CXmentioning
confidence: 99%
“…PLIN2-induced LDs were sensitive to lipolytic stimuli after fasting, and hence, the accumulation of LDs would be reduced despite the high concentrations of FFA in the circulating plasma [97]. Cardiac-specific expression of PLIN2 resulted in slower conduction propagation and induced a higher incidence of atrial fibrillation in aged mice [99].…”
Section: Ldaps and Cardiomyopathymentioning
confidence: 99%